2002
DOI: 10.1212/wnl.58.6.873
|View full text |Cite
|
Sign up to set email alerts
|

Ciguatera fish poisoning

Abstract: Mannitol was not superior to normal saline in relieving symptoms and signs of CP at 24 hours in this study population but had more side effects. These results do not support single-dose mannitol as standard treatment for CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(70 citation statements)
references
References 31 publications
3
63
1
3
Order By: Relevance
“…There is no antidote, supportive therapy is the rule, and survivors recover. Absolute prevention of intoxication depends upon complete abstinence from eating any tropical reef fish, since there is currently no easy way to measure routinely ciguatoxin or maitotoxin in any seafood product prior to consumption, (Nielsen and Tonseth, 1991;Partensky and Sournia, 1986;Partensky et al, 1988;Partensky et al, 1991;Passow, 1991;Perez et al, 2001;Rafuse et al, 2004;Schnorf et al, 2002;Tangen, 1977;Taylor et al, 1995;Tillmann, 2004).…”
Section: Toxins Produced: Ciguatoxin Maitotoxinmentioning
confidence: 99%
See 2 more Smart Citations
“…There is no antidote, supportive therapy is the rule, and survivors recover. Absolute prevention of intoxication depends upon complete abstinence from eating any tropical reef fish, since there is currently no easy way to measure routinely ciguatoxin or maitotoxin in any seafood product prior to consumption, (Nielsen and Tonseth, 1991;Partensky and Sournia, 1986;Partensky et al, 1988;Partensky et al, 1991;Passow, 1991;Perez et al, 2001;Rafuse et al, 2004;Schnorf et al, 2002;Tangen, 1977;Taylor et al, 1995;Tillmann, 2004).…”
Section: Toxins Produced: Ciguatoxin Maitotoxinmentioning
confidence: 99%
“…Monitoring programs (based on Karenia brevis cell counts) generally suffice for preventing human intoxication, except when officials are caught off-guard in previously unaffected areas (Passow, 1991;Perez et al, 2001;Rafuse et al, 2004;Schnorf et al, 2002;Tangen, 1977;Taylor et al, 1995).…”
Section: Toxins Produced: Brevetoxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that mannitol was no better than normal saline. 6 Amitriptyline, lignocaine, mexiletine, gabapentine, nifedipine, calcium gluconate, corticosteroids and vitamin B 12 have also been claimed to be useful by some authors, but without controlled study. 1,5,6,13,15 …”
Section: Discussionmentioning
confidence: 99%
“…It was believed, that because of high osmolarity, mannitol could reduce neuronal edema and act as scavenger of free radicals [10]. However, in some controlled trials, benefit of mannitol over normal saline infusions could not be demonstrated [11]. Besides, osmotic diuresis may worsens a patient's condition by increasing volume depletion.…”
Section: Brief Communication (Original)mentioning
confidence: 99%